Caudal Elbow Luxation in a Dog Managed by Temporary Transarticular External Skeletal Fixation - K. Hamilton; S. Langley-Hobbs; C. Warren-Smith; K. Parsons (Case Reports in Veterinary Medicine)
This case report details a caudal unilateral traumatic elbow luxation in a 4-year-old male neutered Labrador following a road traffic trauma. This is a highly unusual injury in the dog. The pathogenesis and successful treatment by closed reduction followed by stabilisation with a temporary transarticular external skeletal fixator are discussed. The dog was assessed at 4 weeks and 6 months after surgery. Findings at 6 months after treatment demonstrated a normal gait with no pain or crepitation. A mild amount of soft tissue thickening around the elbow was noted. The range of motion of the elbow was limited to 45 degrees of flexion and 150 degrees of extension. This is the first case of a traumatic caudal luxation of the elbow in a dog described in the English veterinary literature and the first report of successful management of an elbow luxation in a dog by closed reduction and temporary transarticular fixation.